Ingestive behavior and performance of female lambs grazing on Marandu palisadegrass under different stocking rates - Vieira Júnior, Luiz Carlos [UNESP]; Cabral, Luciano da Silva; Zervoudakis, Joanis Tilemahos; Abreu, Joadil Gonçalves de; Souza, Alexandre Lima de; Morenz, Mirton José Frota (Sociedade Brasileira de Zootecnia, 2011)
The ingestive behavior and performance of female lambs grazing on Marandu pasture submitted to different stocking rates during the rainy and transition season were evaluated. The experimental area with 4,500 m² was divided into 45 paddocks of 100 m². Twenty-seven Santa Ines female lambs (purebred) with 4 months age and 22 kg of initial body weight were distributed in a completely randomized design, with nine replicates. Lambs were divided into 9 groups with the same initial weight and submitted to three stocking rates: 2, 3 and 4 lambs/paddock, which corresponded to 40, 60 and 80 lambs/ha, respectively. Each group of animals had a module of five paddocks, managed on intermittent grazing system, with 7 days of occupation and 28 d of rest. Increase on time grazing and reduction on time ruminating and resting were observed as stocking rates increased. There was 14% raise in time grazing and 41% decline on time resting by lambs subjected to the highest stocking rate compared with those in the lower stocking rate. The number of animals/ha promoted linear effect on average daily gain, which was higher for animals in the lowest stocking rate of 90 g/d. For gain per area, the best result was obtained with 60 animals/ha featuring an average value of 426 kg/ha.
Keywords: average daily gain; gain per area; grazing; resting; rumination; sheep